The prospects of container industry in the next five years - Wong, Hui Neng (2016)
The global financial crisis impacted the container shipping industry adversely, resulting in one of the worst overcapacity problems in history. However, despite the depressed freight rates, there has been continued delivery of large containerships. As such, analyzing the demand and supply drivers is essential in studying the prospects of container shipping industry in the next five years. Drivers such as the Global Economy, Global Containerized Trade Demand, Containership Scrapping, and Containership Demolition were analyzed. The results revealed that the overcapacity and poor demand growth has led to a change in competition landscape of this industry, price competition had intensified, and capitalizing on market share instead of profitability is the current priority. The continued delivery of large containerships is a measure to improve operational efficiency and survive in the price competition. Therefore, overcapacity will continue to worsen and freight rates are expected to decline in unison in the next five years. The industry may expect more consolidation and capacity rationalization as market players fail to survive the competition.